PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK DALAM PEMBELAJARAN BAHASA MELALUI TEMA BINATANG UNTUK ANAK USIA 4-5 TAHUN DI RA BAHRUL ULUM SAWAHAN TUREN-MALANG - Anis Khamidah; Nikmahtul Khoir Tri Yulia (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2022)
This study aims to develop a pop-up book media that focuses on discussing the language development of children aged 4-5 years in the reading aspect. Using research and development (R&D) methods, which is a research process used to produce certain products, and test the effectiveness of these products. The results of the validation by media experts got a percentage of 98%. Material expert validation I and IIgot a percentage of (I) 96% until (II) 100%. In small and large groups. Observation I got an average score of 42%, then, observation II got an average score of 58%. The results of the large group trial, in observation I got a score of 44%. observation II got a score of 56%. The results of the study show that the pop-up book media deserves to be used as a learning medium that can provide a stimulus to develop aspects of children's language, especially in learning to read. Suggestions for development, to develop pop-up book media products that are visual and digital, can be adjusted to the criteria of early childhood.